2012
DOI: 10.1016/j.semcdb.2011.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Functions and regulation of the APOBEC family of proteins

Abstract: APOBEC1 is a cytidine deaminase that edits messenger RNAs and was the first enzyme in the APOBEC family to be functionally characterized. Under appropriate conditions APOBEC1 also deaminates deoxycytidine in single-stranded DNA (ssDNA). The other ten members of the APOBEC family have not been fully characterized however several have deoxycytidine deaminase activity on ssDNAs. Despite the nucleic acid substrate preferences of different APOBEC proteins, a common feature appears to be their intrinsic ability to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
189
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(191 citation statements)
references
References 147 publications
1
189
0
1
Order By: Relevance
“…(m) and (p) refer to maternal and paternal ko/+ heterozygosity, respectively. Several considerations are relevant: We found a TGCT prevalence of 31.5% in Ter/+ control males on the 129S1/SvImJ background, which represents a significant increase (P < 10 −5 ) compared with the published values (30,38,39). However, the previous studies were performed with a different 129 substrain (129T1/Sv).…”
Section: Transgenerational Interactions Between Apobec1 Ko and Dnd1 Termentioning
confidence: 71%
See 2 more Smart Citations
“…(m) and (p) refer to maternal and paternal ko/+ heterozygosity, respectively. Several considerations are relevant: We found a TGCT prevalence of 31.5% in Ter/+ control males on the 129S1/SvImJ background, which represents a significant increase (P < 10 −5 ) compared with the published values (30,38,39). However, the previous studies were performed with a different 129 substrain (129T1/Sv).…”
Section: Transgenerational Interactions Between Apobec1 Ko and Dnd1 Termentioning
confidence: 71%
“…Dnd1 shares sequence similarity with Apobec1 complementation factor (A1cf) (36), the RNA-binding component of the ApoB RNAediting complex (37,38). This similarity raises the possibility that DND1, like A1CF, functions in RNA editing and in turn that RNA-editing mutants affect TGCT susceptibility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recoding RNA editing by cytidine deamination was thought to be rare in humans, physiologically occurring only in the APOB RNA in intestinal cells mediated by the APOBEC1 cytidine deaminase enzyme. 5 We recently found that transcripts of hundreds of genes coordinately acquire site-specific C-to-U (C > U) RNA editing in peripheral blood monocytes that are exposed to hypoxia and during M1 (proinflammatory) macrophage differentiation. 6 This editing predicts protein recoding in dozens of genes.…”
mentioning
confidence: 99%
“…This family is composed of eleven known members: APOBEC1, APOBEC2, APOBEC3 (further classified as A3A to A3H), APOBEC4, and AID (activation induced deaminase). APOBEC proteins are associated with several functions involving editing of DNA or RNA (reviewed by Smith et al 1 ). APOBEC1 mediates deamination of cytidine at position 6666 of apolipoprotein B mRNA, resulting in the introduction of a premature stop codon and the production of the short form of the protein 2– 4 .…”
Section: Introductionmentioning
confidence: 99%